If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -1b = 90 Solving 3a + -1b = 90 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. 3a + -1b + b = 90 + b Combine like terms: -1b + b = 0 3a + 0 = 90 + b 3a = 90 + b Divide each side by '3'. a = 30 + 0.3333333333b Simplifying a = 30 + 0.3333333333b
| x+5*(3x+10)+10=2 | | -12a+10a=-22 | | 21-2x*3=5 | | 5(3y-13)-4y=-21 | | -6m-10m=-16 | | -24=5b+b | | -25=-10x+5x | | -8n-n=-18 | | 14x-25=12x+25 | | 2n+2+4n=2 | | 6x-1=5x+6 | | -11k+9k=-20 | | -11-2k=1+k | | 4b+10b=28 | | 2(k-3)=6 | | n-13+5n=-25 | | 4u-8=-28 | | x-7-12x=37 | | (14)-(-4)= | | cos(3x-180)=-1 | | 8(b+29)=24 | | g=3f+13 | | -(x-2)+3x=-3(x+4)+15 | | 6=-3+36 | | 41=-5x+6 | | 6+6n=-2-2n | | x=6y+11 | | t^3-3t^2+3t-2=0 | | 4(v+2)-11=9 | | 5x+8y=775 | | 3.5+y=1.05 | | (7p-8)(8p+9)=0 |